Christian theology: an introduction - McGrath, Alister E. (Wiley Blackwell, 2025)
"Christian Theology: An Introduction, Sixth Edition is the best-selling title in the Religion & Theology programme, with 28,819 units sold since publication in October 2016. Considered the most internationally acclaimed textbooks in this area, this work presents Christian theology as a whole rather than focussing on any specific school or denominational form of theology. This is one of the trademarks of this work and it is much appreciated by students and instructors. Retaining the organisation and structure of the sixth edition and its accessible writing style, the proposed new edition will reduce the coverage on older thinkers to focus on modern theologians who made an impact in the field during the period 1980-2010 (e.g. Wolfhart Pannenberg and JuÌ⁸rgen Moltmann) as well as on movements in theology that were influential in the recent past, but whose profile and perceived significance is now fading (such as Radical Orthodoxy). An expanded coverage on non-Western and queer theologies ensures that the book retains its reputation for comprehensiveness, but also shows that we are responding to new trends and voices in the field. For this edition, McGrath is going to be flanked by junior theological educationalist Matthew Thomas, whose research intersects with two of the most important constituencies for the textbook: Catholicism and evangelicalism. As a younger scholar, he will be alert to issues that are relevant to a new generation of students and will ensure the new edition stays ahead of the curve for the years to come"--